“I Like It!” Experiencing Mediascapes in the Artisanship of Prahova County - Marin Constantin (Martor, 2022)
My text is an attempt at developing the heuristic potentialities in the escapology of video recording of anthropological fieldwork and, based on this, in the museum practice of posting videos via social media platforms. Ethnographic information is provided for various crafts from Prahova County (wind-instrument making, weaving, and painting) to illustrate both the artisans’ views of their own craftwork and artefacts and the online responses elicited by such arguments, evidence, ideas, etc. Distinctive and interrelated cultural scenes and dramatis personae are identified and discussed in regards with: (1) doing ethnography and artisan profiles; (2) the museum policy of posting video fieldwork records and interviews; and (3) feedback in the form of predefined emotions and comments from friends, followers, or simply visitors of video posts. The article will provide a theoretical approach to the interpretive continuum and interactive reflexivity between artisans (as bearers of folk culture), museum specialists (as promoters of curatorial and research projects), and the online audience of folk art traditions and museum programs.